The Modelling of Professional Competence Formation Process of Future Specialists in Psychology and Education (Journal of Intellectual Disability - Diagnosis and Treatment, 2018)
In our study, the competence approach to teaching brings out the essence and structure of the professional competence of students in the field of multimedia technologies and in accordance with the definition of new methods, means and forms of education, also the researchers indicate the goal, objectives and content of this process.Depending on the main idea in different years in pedagogy and psychology developed various learning technologies, including targeting the formation of a systematic approach to the tools, techniques and methods of teaching.The ongoing reform of the high education system places high demands on the training of professionals encourages the search for new ways to improve the educational process in high school.